Financial Characteristics of High Performance Companies in Turkey: A Comparative Analysis of Stable Economy in the Financial Crisis Era - Ahmet Turel; Asli Turel; Belverd E. Needles (Journal of Accounting and Management Information Systems (JAMIS), 2012)
Previous research studied characteristics of high performance companies (HPCs) in mature economies (United States, Europe, and Australia) and in an Asian emerging economy (India). This study of HPCs in the developing economy investigates Turkish companies that are listed in the Istanbul Stock Exchange and companies that display specific characteristics of HPCs—sustained and superior cash flow returns, growth rates, and total shareholder returns. We test the hypothesis that there will be no significant difference between the financial performance drivers and measures from before the financial crisis era (2005–2007) and those of after the financial crisis (2008–2009). We identified 41 companies that met the criteria of HPCs over the 2005–2009 time period. When comparing HPCs with ISE ordinary companies, both in the pre-financial crisis period (2005–2007) and the post-financial crisis period 2008–2009, Turkish HPCs were shown to maintain superior asset management and performance profitability, lower financial risk, and stronger cash flow returns compared to the benchmark group over economic periods of rapid growth and stable market conditions and the periods of economic decline and uncertainty. The results provide direction for the management of companies that aspire to HPC status and to maintain HPC status, especially during periods of financial crisis. We identify five operating objectives that are important for maintaining high performance during periods of financial crisis.
Keywords: M41; L25; 650; Financial Analysis; Ratio Analysis; Performance Measurement; Turkey